PENGEMBANGAN PARIWISATA BERBASIS MASYARAKAT (CBT) MENGGUNAKAN KONTRIBUSI CORPORATE SOCIAL RESPONSIBILITY (CSR) DI PEKANBARU PROVINSI RIAU - Wedayanti, Made Devi; Susanti, Heni (WEDANA: Jurnal Kajian Pemerintahan, Politik dan Birokrasi, 2019)
Riau Province has 12 City Regencies and from 12 City Regencies in Riau Province have 58 Potentials and 45 Development Directions. In 2017 Riau Province won the overall prize of the Indonesian Charm Anugerah (API) as a prestigious tourism event at the National level by winning 7 categories. This is an interesting issue to discuss about how the Community-based Tourism Development Strategy in Pekanbaru, Riau Province, with a new model. Furthermore, based on information from the Central Statistics Agency of Riau Province, Riau has a large and medium industrial company which got 219 industries in 2014 and has a micro and small industrial company with 17,435 industries in 2015 and increased from the previous year. Based on information from the Riau Provincial Tourism Office, the phenomenon obtained by researchers from 219 large and medium industries was only 2 companies that implemented CSR in BRI and Telkomsel, and other phenomena related to information from the Riau provincial tourism service from 5 tourism development campaigns. the community is the weakest actor in Riau province. This is what the authors of this research consider. The purpose of this study is to apply the Model of Corporate Social Responsibility Tourism Development (CSR) in Pekanbaru City. This research method is a qualitative descriptive study, a research that aims to describe and analyze the Pekanbaru government in Riau Province in developing community-based tourism (CBT) using the contribution of Corporate Social Responsibility (SCR). Outputs published as publications published in national journals that are not reputed are published in The conclusion in this study is that Community Based Tourism Development uses Corporate Social Responsibility funds very effectively and efficiently in use to support tourism development in Riau Province.